The Creation of Intention To Buy through Online Social Ties and Social Media Advertisement - M. Rifqy Roosdhani; Nurul Komaryatin (Journal of Management and Entrepreneurship Research, 2021)
Objective: The growing number of social media users makes many companies want to get subscribers through their social media activities. There are several choices of strategies that can be done by the company to be able to take the huge market. Research Design & Methods: This study compares the effect of advertising activity on social media and user group development that has a strong tie to intention to buy. Findings: This research found that the social media advertisements has a better impact to intention to buy compared to social ties. Implications & Recommendations: This study was conducted on social media users on land Transportation Company that already has a group in social media, Facebook, and does advertising activities on it. Contribution & Value Added: The results of this study provide theoretical implications in the verification of the previous research results and managerial implications that can help the company in conducting marketing activities through social media.